Analisis Faktor-Faktor yang Memengaruhi Perilaku Menabung pada Gen Z yang Bekerja di Jakarta - Wachyu, Muhammad Daffa Tran; Zahra, Siti Fatimah; Nikensari, Sri Indah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the factors influencing saving behavior among working Generation Z in Jakarta, specifically examining the effects of income level, financial literacy, and self-control. The research is motivated by the phenomenon of consumptive behavior and lifestyle inflation that often accompany increased income, resulting in suboptimal saving rates despite relatively high income levels. This study employs a quantitative approach with a survey method involving 112 Generation Z respondents who are working in Jakarta. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that income level has a positive and significant effect on saving behavior (β = 0.528, t = 5.452, p < 0.001). Financial literacy also has a positive and significant effect on saving behavior (β = 0.255, t = 2.967, p = 0.002). However, self-control does not have a significant effect on saving behavior (β = 0.033, t = 0.283, p = 0.388). Furthermore, self-control is not proven to mediate the relationship between financial literacy and saving behavior. These findings reinforce the Permanent Income Hypothesis and the Theory of Planned Behavior in explaining the saving behavior of the younger generation in urban areas.